CHALLENGES AND SOLUTIONS IN TEACHING ENGLISH USING STEAM TECHNOLOGIES - Irgasheva, Umida (International Conference on Linguistics & Translation, 2025)
The article shows that integrating STEAM technologies into English teaching presents both challenges and opportunities. It is exlpained that while issues like limited resources, lack of training, and time constraints can hinder progress, strategic solutions — including gradual implementation, professional development, and project-based learning — make innovation achievable. By embracing STEAM, English teachers can cultivate critical thinkers, creative communicators, and lifelong learners equipped for the demands of the current century.